Effect of relaxation time, recovery time and extension speed during characterization of LLDPE wrap film properties. Issue 12 (21st September 2022) - Leguebe, Elora; Huart, Victor; Krajka, Nicolas; Pellot, Jérôme; le Baillif, Marie; Erre, Damien
Abstract: Nowadays, product protection during transportation has become essential as import–export is increasing drastically. As a result, wrapping is used to stabilize and protect the goods and must be performed properly. The most commonly used wrapping material is the linear low‐density polyethylene (LLDPE), either manually or through a mechanical equipment. This study will focus on the adequation of stretch film standard to wrapping and transport applications. Both manual and mechanical films were analysed. The anisotropy of the materials was investigated. Characterization of the material was focused on tensile properties, elastic recovery, permanent deformation and stress retention in order to correspond to pallet wrapping applications. It was found that both materials showed anisotropic behaviours. Standard testing conditions were found to not be described properly transport wrapping applications. Relaxation time and extension speed were found to significantly affect hysteresis properties. Abstract : Investigation of the effect testing conditions on measured wrap film properties was performed and confirmed by modelization. Significant differences between real application and testing conditions resulted in the probable unfitness of standard testing for adequate load stabilization optimization.